Ansiedade e problema de manejo de comportamento após tratamento odontológico na primeira infância: revisão de escopo - Alves, Thais Cristina de Souza (2024)
Introduction: Dental fear/anxiety (DFA) and dental behavior management problems (DBMP) in dental care are common during procedures performed in early childhood. This relationship between them has been observed in primary studies, that have specifically evaluated the effect of behavior management techniques and/or specific procedures in reducing DFA and DBMP in children under the age of six. Little is known about the impact of early childhood dental experience on DFA and DBMP in older children. Objective: The objective of this scoping review was to map and synthesize the evidence on the impact of early childhood dental treatment DFA and DBMP throughout childhood. Methods: The search for articles was carried out in the electronic databases APA PsycNet, Cochrane, Embase, LILACS, PubMed, Scopus and Google Scholar. For the search, terms related to preschool children, DFA, DBMP, caries, follow-up were combined. There were no restrictions on the language of publication or date of publication. Clinical trials and longitudinal observational studies carried out with children aged between two and six years at baseline were included. Narrative and systematic reviews, cross-sectional studies, case-controls, case reports and series, clinical trial protocols, abstracts in conference proceedings, editorials and opinion pieces were excluded. The process of selecting studies and extracting information was carried out by two researchers. Information on the treatments carried out, management techniques and follow-up time was extracted from the studies and summarized in a chart and text. Results: Out of a total of 742 studies identified, nine were included, of which five were randomized clinical trials, one was a non-randomized clinical trial and three were prospective longitudinal studies. The change in DFA level after dental care in early childhood was measured in six studies. In three there was an improvement. In the others, the DFA level worsened (n=2) or there was no change (n=1). In the other studies, DBMP was measured in isolation or in conjunction with DFA. Of the three, two showed an improvement in behavior. Follow-up times ranged from seven days to 30 months. Conclusion: From the studies selected, it was noted that there is no consensus on the effect of dental treatment carried out in early childhood on DFA and DBMP at future visits. The number of studies is limited, and the methods and results are heterogeneous.